Pembentukan karakter kedisiplinan peserta didik melalui pembiasaan apel pagi di MTs Tarbiyatul Banin Banat Tuban - Afaliyah, Khoirotul (Maliki Interdisciplinary Journal, 2024)
At this time the character of the current generation has begun to fade. With the emergence of juvenile delinquency in society. Therefore, there is a need for character education from the start of adolescence, to be precise during madrasah. The aim of the research is to determine the implementation and benefits of morning assembly activities as a form of student discipline character at MTs Tarbiyatul Banin Banat. The method used is descriptive qualitative by collecting data through interviews, observation and documentation. The results of research on the implementation of routine morning assembly can instill the character of discipline, as proven by the results of observations made that the discipline of students at this madrasah is good. The benefits are to instill discipline, increase knowledge, interests and talents and develop skills in students.